Vaccination of classmates for an immunosuppressed child's protection in a school in the LHA Roma 1. (13th November 2019) - Marino, M; Spadea, A; Furia, G; Frisicale, E M; Michelazzo, M B; Valentini, F; Consoli, C; Forte, U; Bracci, S; Goletti, M
Abstract: Issue/problem: One of the duty of a State is to guarantee the protection of the health of all citizens, both safeguarding the sick individual needing care and protecting the healthy individual. An important objective of the vaccination prevention programs is to protect people most at risk of contracting infections because of their health conditions. Description of the problem: In April 2019 the District 14 of Local Health Autority Roma 1 was asked by a father of an immunosuppressed child (6 years old), worried about infectious diseases, to verify the safeness of his child school attendance (the first class of primary school). First, a list of the class mates was asked to the school, in order to check their vaccination status by interrogating the web based regional vaccination register. Then, the District asked to the school to plan a meeting with classmates' parents and teachers, in order to inform about the importance of a complete immunization both for the classmates and the immunosuppressed child protection. Results: Preliminary results show that, among 18 classmates, 77.8% had full vaccination coverage for the second dose measles and fourth dose whooping cough (not mandatory for children aged less than 7 years), 22.2% were immunized for chicken pox. Among the parents attending the meeting, 15 agreed to complete their children vaccination cycle, all the teachers agreed to undergo whooping cough and chicken pox vaccination in order to allow a safe school attendance to the immunosuppressed child. Parents and teachers were given an appointment in a vaccination center for the week following the meeting. Lessons: It is important to promote a real 'vaccination culture' starting from the school, in order to develop greater citizenship awareness about the potential of vaccinations and to contrast fake news and ignorance leading to dangerous prejudices. Key messages: The active collaboration between institutions (sanitary and school) allows, through the integration between different competences, to achieve health objectives to protect the community. Talking to pupils' parents about infectious diseases and their prevention makes it possible to increase knowledge and therefore awareness of the importance of adult and children health protection.